III. THE ORGANIZATION OF ATTACHMENT BEHAVIOR IN EARLY CHILDHOOD: LINKS WITH MATERNAL SENSITIVITY AND CHILD ATTACHMENT REPRESENTATIONS. Issue 4 (5th December 2018) - Posada, Germán E.; Trumbell, Jill M.; Lu, Ting; Kaloustian, Garene
ABSTRACT: This article investigated two central questions about mother–child attachment relationships during early childhood: (1) the association between maternal sensitivity and child attachment behavior (Study 1) and (2) the link between child attachment behavior and representations (Study 2). In Study 1, maternal sensitivity and child security were assessed in naturalistic contexts among 74 middle‐class dyads, when children were about 3.5 and again 5.5 years of age, using the Maternal Behavior with Preschoolers Q‐set (MBPQS) and the Attachment Q‐set (AQS), respectively. Sensitivity and security were significantly related at each point in time and stable from 3.5 to 5.5 years of age. Furthermore, changes in sensitivity predicted changes in child security. In Study 2, the relationship between the organization of preschoolers' attachment behavior and the structure of attachment representations (secure base script knowledge) was assessed. Participants were 158 preschoolers between 3 and 5.5 years. Children's secure base behavior was described with the AQS, whereas their attachment script knowledge was assessed with the MacArthur Attachment Story Completion Task. The organization of children's secure base behavior was significantly, if modestly, associated with their knowledge of the secure base script.